РАБОТЫ ПРОВОДИМЫЕ ПО ИЗУЧЕНИЮ ИНОСТРАННЫХЯЗЫКОВ В АКАДЕМИЧЕСКИХ ЛИЦЕЯХ РЕСПУБЛИКИ УЗБЕКИСТАН - Бабаниязова, Н.П. (SCIENCE and SOCIETY, 2016)
The article deals with the issues of teaching foreign language to the students of academics lyceums. Tasks put forward by the State Educational Standard on the system of continuous education are presented in the work. Attempt to analyze the current model programs for the realization of state educational standards to work out the appropriate methods of teaching the students of academic lyceums have been done. The author of the article emphasizes the advantages of using modular technology in academic lyceums.
Keywords: the academic lyceum; the state educational standard; the typical program; the methods of teaching; teaching of foreign languages; requirements; graduates; technology of modular training